2014
DOI: 10.1371/journal.pone.0113420
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Behavioral Characterization of D-473, an Orally Active Triple Reuptake Inhibitor Targeting Dopamine, Serotonin and Norepinephrine Transporters

Abstract: Major depressive disorder (MDD) is a debilitating disease affecting a wide cross section of people around the world. The current therapy for depression is less than adequate and there is a considerable unmet need for more efficacious treatment. Dopamine has been shown to play a significant role in depression including production of anhedonia which has been one of the untreated symptoms in MDD. It has been hypothesized that drugs acting at all three monoamine transporters including dopamine transporter should p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[44, 45] Recently, we have reported development of an orally active TRI, D-473 (Figure 1), which exhibited efficacious activity in FST and elevated level of all three monoamines in a microdialysis study. 46 …”
Section: Resultsmentioning
confidence: 99%
“…[44, 45] Recently, we have reported development of an orally active TRI, D-473 (Figure 1), which exhibited efficacious activity in FST and elevated level of all three monoamines in a microdialysis study. 46 …”
Section: Resultsmentioning
confidence: 99%
“…More recently, it was found that depressed patients had greater DAT expression on both sides of the striatum and that bupropion's treatment reduced significantly DAT binding in the striatum [82]. Also, the triple reuptake inhibitors JZAD-IV-22, TP1, and D-473 that block the dopamine, norepinephrine, and serotonin transporters exhibited antidepressant-like efficacy in the FST and/or TST without locomotor stimulant or sensitization properties [83][84][85]. However, deep brain stimulation of the medial forebrain bundle in male Wistar rats showed a significant increase in swimming duration, that was associated to a significant increase in DAT protein expression in the hippocampus [86].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we demonstrated successful development of orally active TRIs which exhibited high efficacy in the rat animal model of depression. 28,29 Furthermore, we have recently shown that the novel TRI D-578 exhibits greater efficacy than that of paroxetine in normalizing traumatic-stress-induced extinction learning in the single prolonged stress (SPS) rat model of PTSD. 28 D-578 also produces robust and efficacious antidepressant effects in the forced swim test without confounding locomotor effects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21,24−27 Two orally active lead TRIs, D-473 and D-578 (Figure 1), exhibited high efficacy in the depression and PTSD animal models. 28,29 In this regard, these compounds were more efficacious than the reference drugs. In another line of experiments, we developed a number of potent DNRI-type compounds which gave us an indication for the structural requirement for such an activity in pyran derivatives.…”
Section: ■ Introductionmentioning
confidence: 90%